2020
DOI: 10.1186/s12934-020-01350-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineered butyrate-producing bacteria prevents high fat diet-induced obesity in mice

Abstract: Background: Obesity is a major problem worldwide and severely affects public safety. As a metabolite of gut microbiota, endogenous butyric acid participates in energy and material metabolism. Considering the serious side effects and weight regain associated with existing weight loss interventions, novel strategies are urgently needed for prevention and treatment of obesity. Results: In the present study, we engineered Bacillus subtilis SCK6 to exhibited enhanced butyric acid production. Compared to the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 58 publications
5
28
0
1
Order By: Relevance
“…Butanoic acid is generally produced by the metabolism of the bacteria in the intestine [41]. researchers have shown that feeding mice with engineered Bacillus subtilis SCK6, which produces butanoic acid, can cause reduced food intake and weight loss in mice [42]. And we found that the butanoic acid content in AF feces was 13.56 times higher than that of the MF feces.…”
Section: Certain Metabolites Were More Abundant In the Feces Of The Amentioning
confidence: 64%
“…Butanoic acid is generally produced by the metabolism of the bacteria in the intestine [41]. researchers have shown that feeding mice with engineered Bacillus subtilis SCK6, which produces butanoic acid, can cause reduced food intake and weight loss in mice [42]. And we found that the butanoic acid content in AF feces was 13.56 times higher than that of the MF feces.…”
Section: Certain Metabolites Were More Abundant In the Feces Of The Amentioning
confidence: 64%
“…Our findings that n-butyrate inhibited HDAC activity and that HDAC activity is required for endometriotic cell growth are consistent with studies reporting elevated HDAC1 expression in lesions from women with endometriosis ( 85 , 86 ). Thus, future efforts could be directed at delivering HDAC inhibitors, bacteria engineered to over-produce n-butyrate ( 87 , 88 ), n-butyrate producing Lactobacillus strains ( 81 ), or n-butyrate analogs to treat endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Bacillus strains used in the study are shown in Table 1. Wild-type B. subtilis sck6 (BS) and engineered butyrate-producing B. subtilis sck6 (BsS-RS06550, BPBS) was engineered by Dr. Liang Bai (Bai et al 2020). Single colonies of BS and BPBS strains were cultured in LB broth at 37 °C overnight with shaking (200 rpm).…”
Section: Bacterial Strains and Culturesmentioning
confidence: 99%